Application of Acid and Cold Stresses to Enhance the Production of Clavulanic Acid by Streptomyces clavuligerus - Rodrigues, K. C.S.; Costa, C. L.L.; Badino, A. C.; Pedrolli, D. B. [UNESP]; Pereira, J. F.B. [UNESP]; Cerri, M. O. [UNESP] (Springer Nature, 2019)
Clavulanic acid (CA) is frequently prescribed for treatment of bacterial infections. Despite the large number of studies concerning CA production, there is still a need to search for more effective and productive processes because it is mainly produced by biochemical route and is chemically unstable. This paper evaluates the influence of acid and cold stresses on CA production by Streptomyces clavuligerus in bench scale stirred tank bioreactor. Four batch cultures were conducted at constant pH (6.8 or 6.3) and temperature (30, 25, or 20 °C) and five batch cultures were performed with application of acid stress (pH reduction from 6.8 to 6.3), cold stress (reduction from 30 to 20 °C), or both. The highest maximum CA concentration (684.4 mg L−1) was obtained in the culture conducted at constant temperature of 20 °C. However, the culture under acid stress, in which the pH was reduced from 6.8 to 6.3 at a rate of 0.1 pH unit every 6 h, provided the most promising result, exhibiting a global yield coefficient of CA relative to cell formation (YCA/X) of 851.1 mgCA gX−1. High YCA/X values indicate that a small number of cells are able to produce a large amount of antibiotic with formation of smaller amounts of side byproducts. This could be especially attractive for decreasing the complexity and cost of the downstream processing, enhancing CA production.
Keywords: Acid stress; Batch fermentation; Clavulanic acid; Cold stress; Process enhancing; Streptomyces clavuligerus; Stress induction